Kecimol Music As Cultural Identification Of Sasak Ethnic - I Gede Yudarta; I Nyoman Pasek (Institut Seni Indonesia Denpasar, 2017)
Music is one of the arts in West Nusa Tenggara region, precisely in Lombok Island. In that region there are two types of Kecimol, modern and traditional. The existence of these two types of cimol is very contradictory. The existence of these two types of kecimol is in compatible. The existence of modern kecimol is much more popular than the traditional one in the community life. The occurrence of the above phenomena arose the desire to raise the traditional kecimol music as an object of study with the aim to elevate the existence of the music as a cultural attraction that contains Sasak cultural values. This study is the initial step to understand the existence of kecimol music because of several topics to be discussed such as: background and history of the existence of ketimol music, its shape, structure and function in community life.